Multifunctional chitosan/carbon dots/sodium alginate/zinc oxide double-layer sponge hydrogel with high antibacterial, mechanical and hemostatic properties - Reza Monfared-Hajishirkiaee; Hamide Ehtesabi; Shima Najafinobar; Zahra Masoumian (Elsevier, 2023)
Due to the fact that bacterial contamination of wounds is the cause of increased morbidity and mortality today, various antimicrobial wound dressings are developing to prevent wound contamination. In addition, an ideal wound dressing should have proper mechanical and hemostatic properties to maintain wound healing conditions. Here, a double-layer sponge hydrogel nanocomposite wound dressing was designed and manufactured by combining zinc oxide nanoparticles (ZnONPs) with different concentrations in the hydrogel layer and green carbon dots in the sponge layer. The surface morphology of two layers was investigated using a scanning electron microscope. X-ray diffraction proved the presence of ZnONPs. Physical tests showed a decrease in water absorption and water vapor transmission rate and an increase in blood absorption in the presence of ZnO. The sponge layer showed suitable absorption support in the presence of carbon dots. By combining nanoparticles in both layers, the mechanical properties were greatly enhanced. The sponge hydrogel with the highest concentration of ZnO showed excellent inhibition of 41 mm against Pseudomonas aeruginosa bacteria and 25 mm of inhibition against Staphylococcus aureus. Finally, in vitro blood clotting and animal tests confirmed the increase in the hemostatic power of the sponge hydrogel with the maximum concentration of ZnO.